Thermal and mechanical properties of melt processed intercalated poly(methyl methacrylate)-organoclay nanocomposites over a wide range of filler loading - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer International, 2008)
BACKGROUND: Poly(methyl methacrylate) (PMMA)-organoclay nanocomposites with octadecylammonium, ion-modified montmorillonite, prepared via melt processing, over a wide range of filler loading (2-16 wt%) were investigated in detail. These hybrids were characterized for their dispersion structure, and thermal and mechanical properties, such as tensile modulus (E). break stress (sigma(brk)), percent break strain (epsilon(brk)) and ductility(J), using wide-angle X-ray diffraction, transmission electron microscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and tensile and impact tests. RESULTS: Intercalated nanocomposites were formed even in the presence of 16 wt% clay (high loading) in PMMA matrix. PMMA intercalated into the galleries of the organically modified clay, with a change in d-spacing in the range 11-16 angstrom. TGA results showed improved thermal stability of the nanocomposites. The glass transition temperature (T-g) of the nanocomposites, from DSC measurements, was 2-3 degrees C higher than that of PMMA. The ultimate tensile strength and impact strength decreased with increasing clay fraction. Tensile modulus for the nanocomposites increased by a significant amount (113%) at the highest level of clay fraction (16 wt%) studied. CONCLUSION: We show for the first time the formation of intercalated PMMA nanocomposites with alkylammonium-modified clays at high clay loadings (> 15wt%). Tensile modulus increases linearly with clay fraction, and the enhancement in modulus is significant. A linear correlation between tensile strength and strainat-break is shown. Thermal properties are not affected appreciably. Organoclay can be dispersed well even at high clay fractions to form nanocomposites with superior bulk properties of practical interest. (c) 2007 Society of Chemical Industry.
Keywords: impact strength; mechanical properties; Nanocomposites; PMMA; Thermal properties